How the Golem Came to Prague - Dekel, Edan (The Jewish quarterly review, 2013)
This article examines the emergence of the Golem legend associated with the Maharal of Prague in the first half of the nineteenth century, with specific attention to the innovations found in two little-known versions by important Jewish literary figures of the era: the Bohemian-born Viennese poet and editor Ludwig Frankl and the Danish writer Meir Aaron Goldschmidt. These versions, it is argued, reveal several crucial mechanisms that help explain the shift from a Golem tale distributed among various individual places and rabbis, to one with little or no specificity at all, and finally to the Prague version that dominates the subsequent literary and artistic manifestations of the legend. The proliferation of non-Jewish renditions of the legend in the first quarter of the century, starting with the folklorist Jakob Grimm’s brief report in 1808, provides a context for several Jewish reconfigurations of the material around the centrality of Prague and its most famous rabbi, the Maharal. By 1847, the transition is complete with the near-canonical version published by Leopold Weisel in the popular and influential anthology of Bohemian Jewish tales, Sippurim. But in the decade leading up to Weisel’s publication, Frankl and Goldschmidt both produce intricate and sophisticated versions that offer a glimpse into the motifs and techniques engaged by the Jewish literary imagination of the period.